The strategic case for establishing public-private partnerships in cancer care. Issue 1 (December 2015) - Holden, Debra; Reiter, Kristin; O'Brien, Donna; Dalton, Kathleen
Abstract Background In 2007, the National Cancer Institute (NCI) launched the NCI Community Cancer Centers Program (NCCCP) as a public-private partnership with community hospitals with a goal of advancing cancer care and research. In order to leverage federal dollars in a time of limited resources, matching funds from each participating hospital were required. The purpose of this paper is to examine hospitals' level of and rationale for co-investment in this partnership, and whether there is an association between hospitals' co-investment and achievement of strategic goals. Methods Analysis using a comparative case study and micro-cost data was conducted as part of a comprehensive evaluation of the NCCCP pilot to determine the level of co-investment made in support of NCI's goals. In-person or telephone interviews with key informants were conducted at 10 participating hospital and system sites during the first and final years of implementation. Micro-cost data were collected annually from each site from 2007 to 2010. Self-reported data from each awardee are presented on patient volume and physician counts, while secondary data are used to examine the local Medicare market share. Results The rationale expressed by interviewees for participation in a public-private partnership with NCI included expectations of increased market share, higher patient volumes, and enhanced opportunities for cancer physician recruitment as a result of affiliation with the NCI. On average, hospitals invested resources into the NCCCP at a level exceeding $3 for every $1 of federal funds. Six sites experienced a statistically significant change in their Medicare market share. Cancer patient volume increased by as much as one-third from Year 1 to Year 3 for eight of the sites. Nine sites reported an increase in key cancer physician recruitment. Conclusions Demonstrated investments in cancer care and research were associated with increases in cancer patient volume and perhaps in recruitment of key cancer physicians, but not in increased Medicare market share. Although the results reflect a small sample of hospitals, findings suggest that hospital executives believe there to be a strategic case for a public-private partnership as demonstrated through the NCCCP, which leveraged federal funds to support mutual goals for advancing cancer care and research.